l-Carnitine enhances exercise endurance capacity by promoting muscle oxidative metabolism in mice - Kim, Jun Ho; Pan, Jeong Hoon; Lee, Eui Seop; Kim, Young Jun (Biochemical and biophysical research communications, 2015)
l-Carnitine (LC), the bioactive form of carnitine, has been shown to play a key role in muscle fuel metabolism during exercise, resulting in increased fatty acid oxidation and energy expenditure. However, whether LC contributes to improved endurance exercise performance remains controversial. This study was designed to investigate the effects of LC administration on endurance capacity and energy metabolism in mice during treadmill exercise. Male C57BL/6 mice were divided into two groups (sedentary and exercise) and received daily oral administration of LC (150 mg/kg) or vehicle with a high-fat diet for 3 weeks. During the experimental period, all animals were trained three times a week on a motorized treadmill, and the total running time until exhaustion was used as the index of endurance capacity. LC administration induced a significant increase in maximum running time with a reduction of body fat compared with the control group when mice were subjected to programmed exercise. The serum levels of triglyceride, non-esterified fatty acid, and urea nitrogen were significantly lower in the LC group than the corresponding levels in the control group, while serum ketone body levels were higher in the LC group. Muscle glycogen content of LC administered-mice was higher than that of control mice, concomitant with reduced triglyceride content. Importantly, muscle mRNA and protein expressions revealed enhanced fatty acid uptake and oxidative metabolism and increased mitochondrial biogenesis by LC administration. These results suggest that LC administration promotes fat oxidation and mitochondrial biogenesis while sparing stored glycogen in skeletal muscle during prolonged exercise, resulting in enhanced endurance capacity. •l-Carnitine enhances running endurance capacity in exercise-trained mice.•l-Carnitine promotes muscle oxidative metabolism while sparing glycogen consumption.•l-Carnitine increases markers of mitochondrial biogenesis in skeletal muscle.